Competition and Efficiency in EU Banking - Tsiritakis, Emmanuel (SPOUDAI Journal of Economics and Business, 2017)
On the road to the new landscape in EU banking brought on by the financial crisis we assess the relationship between the level of competitiveness and efficiency. We estimate X-inefficiency for a sample of banks operating in the European Union using the stochastic frontier approach. We relate efficiency levels to market competitiveness employing Panzar & Rosse’s H statistic for three clusters of banks constructed according to their efficiency scores. In addition, we examine the impact of efficiency, as well as concentration, on banking competition measured by the Net Interest Margin (NIM), controlling for bank specific factors. Overall we find that larger banks tend to be more efficient. In contrast, it seems that there exists a group of smaller banks in our sample that are ‘relationship’, ‘niche’ or ‘regionally’ protected from the hazards of competition and are X-inefficient. Moreover, the efficient group of banks entertains increases in NIM as they get more efficient, indicating that efficiency gains are not passed on to customers. JEL Classification: G20, G21, L10